Integrated method of analysis, visualization, and hardware for ship motion simulation. Issue 3 (20th December 2017) - Ham, Seung-Ho; Roh, Myung-Il; Zhao, Luman
Graphical abstract: Abstract: Traditionally, graphs were the only way to show the results of ship motion analyses. They did not usually impose any feeling about how fast the ship could move or how large the positions of the ship changed. Currently, integrated simulations combining physics-based analyses with IT technologies, such as virtual reality (VR), motion platforms, or other hardware, can offer a potential solution. In ship motion analyses, the dynamic ship response can be obtained by considering the environmental loads, such as ocean waves, and VR technology can be used to visualize the analysis results in the virtual world. We can see the ship motion relative to textures of real objects, including the water and sky, as if in the real world. The results calculated from the ship motion analysis can also be transferred to the motion platform to generate realistic movements. However, it is not easy to integrate three different technologies in one system because they have different purposes and have been developed individually. To solve this problem, an integrated simulation framework based on three different technologies is proposed. The proposed framework can be used to synchronize the simulation time and exchange the data through the middleware using a standardized data structure. Furthermore, we can easily add new components or remove the existing components in the simulation. To verify the efficiency and applicability of the proposed framework, the motion simulation of a drillship is applied.